On the comparison of lightning fatality rates between states in Malaysia from 2008-2019 - Syakura A.R.; Izadi M.; Osman M.; Ab Kadir M.Z.A.; Elistina A.B.; Gomes C.; Jasni J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Disasters; Fatalities; Flash; Lightning density; Lightning injury; Natural disasters; Lightning